Analisis Sistem Pengendalian Internal Pada PT Kalbe Farma Tbk Melalui Pendekatan COSO Framework - Permatasari, Santi (POLITEKNIK LP3I, 2024)
PT Kalbe Farma Tbk is one of the companies listed on the Indonesia Stock Exchange (IDX). PT Kalbe Farma Tbk was established in 1966, has come a long way from its beginnings as a pharmaceutical business managed in the garage of the founder's house in the North Jakarta area. The company must actively make improvements to the parts that are the weak points of the company in order to achieve the company's ultimate goal. Maintenance or supervision is needed so that the company can continue to grow. The improvements and supervision that the company can make stem from the internal controls that the company has implemented. Internal control is a process designed by a business unit or company with the aim of achieving company efficiency and effectiveness. Based on the description above, the author is interested in analyzing the internal control system at PT Kalbe Farma Tbk using an approache, namely COSO Framework. By analyzing the internal control system using an approache COSO Framework, it is hoped that it can understand element of COSO Framework to be analyzed.